Pseudo-Media Sites, Polarization, and Pandemic Skepticism in Spain - Palau-Sampio, Dolors (Frontiers in Political Science, 2021)
The Coronavirus pandemic has triggered an authentic infodemic, which is a global epidemic of disinformation that has spread throughout most of the world. Social media platforms and pseudo-media outlets have contributed to the problem by producing and disseminating misleading content that is potentially dangerous to public health. This research focuses on a rather unknown phenomenon, which involves digital sites that mimic the appearance of news media but provide pseudo-information. Five Spanish pseudo-media have been analyzed with the aim of enhancing understanding of the issues and the frames presented. The results show clear links with the far-right ideology as well as the presence of a populist, polarized discourse through the use of belligerent, offensive expressions to refer to institutions and their representatives. Politics is the main issue represented, with a frame that clearly points out the incompetence and cynicism of the Spanish government. Conspiracy theories associate the origins of the pandemic to a Chinese laboratory and emphasize a global plan to establish systemic control. Measures to stop the virus are framed as harmful and ineffective, linked to a euthanasia scheme targeted at older people, especially regarding vaccination, which is presented as a solution offered for economic interests.